CAR-T cell persistence in the treatment of leukemia and lymphoma. Issue 11 (19th September 2021) - Gupta, Arjun; Gill, Saar
Abstract: Chimeric antigen receptor (CAR) T cells have emerged as a powerful therapeutic modality for cancer. Following encouraging clinical results, autologous anti-CD19 CAR-T cells first secured regulatory approval from the U.S. Food and Drug Administration in 2017 for the treatment of pediatric B cell acute lymphoblastic leukemia and for diffuse large B cell lymphoma (DLBCL), followed recently by mantle cell lymphoma. While long-term immunosurveillance is among the most important requirements for durable remissions in leukemia and a major potential benefit of immunotherapy, the exact determinants of CAR-T cell persistence remain elusive. Furthermore, it is less clear that long-term persistence is required for durable remission in lymphoma. In this review, we aim to describe the factors governing CAR-T cell persistence as well as unique approaches to exert control over engineered lymphocyte populations post-infusion. Additionally, we explore potential risks and associated clinical considerations arising from prolonged surveillance by highly reactive cytotoxic T lymphocytes.